PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE QUIZ TEAMUNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIKDI KELAS XSMA NEGERI 2 XIII KOTO KAMPAR - Amran, Elva Yasmi Amran Yasmi; Haryati, Sri Haryati Sri; Murwani, Amelia Murwani Amelia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The Research about  application ofactive learning strategyQuiz Team has beendonetoknow the improvement student’s achievementon the topicofatomic structure and system of periodic unsure atclassX ofSMA Negeri 2 XIII Koto KamparinAugust 2013. This research is experimental research based on pretest-posttest design. The sample consistedoftwoclasses, X-2 classas control classandX-1classas experiment class that randomly selectedaftertesting normality and homogeneity test. Active learning strategyQuiz Teamapplied in X-1 class. Analysis ofdata usedt-test. Results of data processing obtainedtcount>ttable (3,23>1,67). Itmeans thatthe application ofactive learning strategy Quiz Team canimprove student’s achievementon the topic ofatomic structure and system of periodic unsure atclass X ofSMANegeri 2 XIII Koto Kampar. The improvement of student’s achievement in experiment class was supported byKp score 16,45%. Keyword :Active Learning, Quiz Team, Atomic Structure and System of Periodic